2017
DOI: 10.1016/j.pan.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular alterations contributing to pancreatic cancer chemoresistance

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most common causes of cancer-related death all over the world. This disease is difficult to treat and patients have an overall 5-year survival rate of less than 5%. Although two drugs, gemcitabine (GEM) and 5-fluorouracil (5-FU) have been shown to improve the survival rate of patients systematically, they do not increase general survival to a clinically acceptable degree. Lack of ideal clinical response of pancreatic cancer patients to chemotherapy is likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 92 publications
0
24
0
Order By: Relevance
“…The relatively low frequency of complete remissions in neo‐adjuvant trials underscores this as an important clinical issue . Exposure of PDAC cells to components of chemoradiotherapy results in several mechanisms contributing to resistance including activation of survival and anti‐apoptotic pathways . This report uses a novel pharmacologic approach to augment the direct effects of chemoradiotherapy in a series of pre‐clinical PDAC models.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low frequency of complete remissions in neo‐adjuvant trials underscores this as an important clinical issue . Exposure of PDAC cells to components of chemoradiotherapy results in several mechanisms contributing to resistance including activation of survival and anti‐apoptotic pathways . This report uses a novel pharmacologic approach to augment the direct effects of chemoradiotherapy in a series of pre‐clinical PDAC models.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, with the emergence of gemcitabine and fluorouracil resistance, the therapeutic efficacy of GEM in pancreatic cancer is declining [7,8]. Recent research on PDA pointed out that the abnormal expression of genes or proteins plays an important role in the occurrence and development of this tumor [9,10]. In general, it is urgent to deepen the understanding of the molecular mechanism of PDA and find new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [14] found that six circulating miRNAs are correlated with overall survival in castration-resistant prostate cancer. Other studies have reported the molecular function and potential clinical utility of miRNAs in PDAC [15,16]. However, the molecular mechanism of miRNAs in pancreatic carcinogenesis remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%